PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR CABANG PT. TELKOM KABUPATEN JEMBRANA BALI - Putri Anggreni (Forum Manajemen, 2017)
This study aims to determine whether there is significant influence between motivation on employee performance at the branch office of PT. Telkom Jembrana Bali. In this study used a sample of 20 respondents with a random sampling technique and using descriptive analysis method which consists of two variabels, namely, motivation of employee as independent variables (X) and employee performance as dependent variables (Y). To collect data that is done is interview, documentation, and a questionnaire in the branch office of PT. Telkom Jembrana regency of Bali, and analyzed by qualitative and quantitative analysis techniques using test calculations F and t test. The findings of this study is to test the value of X1 states that t tarithmetic < ttable (3,3776 < 2,101) it means refusing Ho and accept H1, meaning that there is significant influence between motivation with employee performance. Of test results F stated that Faruthmetic > Ftable (0,001 > 0,05) with a level of 5% and freedom 18. And views of the coefficient of determination obtained for 0,042 means that the level of the performance of employees in the branch office of PT. Telkom Jembrana regency of Bali can be explained 44,2% of the variable motivation.